Efektifitas Pemberian Health Education Tentang Pencegahan Covid 19 Dan 5M Dalam Menurunkan Tingkat Kecemasan - Yeni Nur Rahmayanti; Christiana Arin Prorini; Pipi Anonyma; Ima Arifa (Universitas Duta Bangsa Surakarta, 2022)
Abstract The spread of Covid-19 through small droplets of saliva that come out of the nose or mouth when a person infected with Covid-19 sneezes or coughs. Masks when traveling, maintaining distance and implementing health protocols. The purpose of this study was to determine whether there was an effect of the coronavirus disease 2019 (covid-19) pandemic on the level of public anxiety in the Mojorejo village. This study uses a quantitative descriptive method. The purpose of the study was a significant difference in the effectiveness of providing health education regarding the prevention of Covid 19 and 5M in reducing the level of anxiety in the residents of Dukuh Mojorejo in Sukoharjo Regency. This study uses a quasi-experimental approach, namely one group pre-test and post-test approaches. The sampling technique used is Simple Random Sampling, as many as 60 respondents. The results before giving Health Education about Prevention of Covid 19 and 5m were the most with moderate anxiety of 39 people (65%) and after the Provision of Health Education about Prevention of Covid 19 the most low anxiety was 41 people (68.3) with a t count of 10, 40 and the -value is 0.001 because (p <0.05) it is concluded that there is an Effectiveness of Providing Health Education About Covid 19 Prevention in Reducing Anxiety Levels